Effect of Palm Stearin Supplementation on the Haematological and Blood Biochemical Indices in Growing Buffaloes - , Adis Mirel Ahmed; , Vishwa Bandhu Chaturvedi (Archives of Current Research International, 2025)
The present study aimed to assess the impact of Palm stearin (PS), a byproduct of palm oil refining industry on the haematological and blood biochemical profile of growing buffaloes. Eighteen healthy buffalo calves were randomly assigned to three dietary treatment groups (n=6 per group): T₀ (control), T₁, and T₂. The control group (T₀) was provided a basal diet without PS, while the T₁ and T₂ groups received concentrate mixtures supplemented with 3% and 6% PS, respectively. The feeding trial was conducted over 165 days and during which all animals were fed a balanced diet consisting of a 50:50 ratio of concentrate mixture and wheat straw, formulated according to the Indian Council of Agricultural Research (ICAR, 2013) standard. To fulfil the vitamin A requirements, each animal also received a small amount (1–2 kg) of green fodder twice a week. Blood samples were collected at three time points: day 0, day 80, and day 160 and the samples were analysed for various haematological and biochemical parameters. The results showed that supplementation with Palm stearin (PS) had no significant effect (P > 0.05) on most of the blood parameters including haemoglobin (Hb), packed cell volume (PCV), glucose, triglycerides, total protein, albumin, globulin, albumin-to-globulin ratio (A: G), urea, high density lipoprotein (HDL), low density lipoprotein (LDL), aspartate aminotransferase (AST), and alanine aminotransferase (ALT). However, a significant increase (P < 0.001) in Total Cholesterol was observed in the groups supplemented with PS. These findings indicate that dietary addition of Palm stearin (PS) at levels of 3% and 6% in the concentrate mixture (approximately 1.5% and 3% of the total diet) alters cholesterol levels without negatively impacting liver function or other key blood indices. Thus, Palm stearin (PS) appears to be a safe and potentially beneficial fat source for growing buffaloes thereby offering a sustainable alternative energy source in the livestock feeding strategies.